Morality and Religion - Arsic, Milos V. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
It is often argued, especially in polemics, that morality makes no sense if it is not grounded in faith. However, the question is whether religious beliefs and customs shape moral behavior? Is religion necessary for morality? The intersection of morals and religion involves the relationship between religious views and morals. It is common for religions to have value frameworks that aim to guide adherents in determining between right and wrong. The aim of this theoretical research is the presentation, ie the analysis of morals and religion. The need to choose the mentioned subject of research is imposed by its importance, insufficient research and the necessity of re-examination in the modern epoch of the crisis of the value system. Defining the similarities and differences between morals and religion, as well as their interpretation, is fundamental for understanding their relationship. Many scientific studies have failed to break down "morality" and "religion" into theoretically grounded elements. It is believed that the categories of "morality" and "religion" must be separated, in order to get a complete picture of complex interaction as a roadmap for future research into the relationship between morality and religion. Essentially, traditional moral values are based on spiritual values. That is why it is necessary to accept the universality of both the moral and the religious in every person, not only historically but also in the context of modernity and anticipated human future.
Keywords: morality; religion; moral norms; religious dogmas